Space, Imagination and the Cosmos from Antiquity to the Early Modern Period (Studies in History and Philosophy of Science,, 2018)
This volume provides a much needed, historically accurate narrative of the development of theories of space up to the beginning of the eighteenth century. It studies conceptions of space that were implicitly or explicitly entailed by ancient, medieval and early modern representations of the cosmos. The authors reassess Alexandre Koyré's groundbreaking work From the Closed World to the Infinite Universe (1957) and they trace the permanence of arguments to be found throughout the Middle Ages and beyond. By adopting a long timescale, this book sheds new light on the continuity between various cosmological representations and their impact on the ontology and epistemology of space. Readers may explore the work of a variety of authors including Aristotle, Epicurus, Henry of Ghent, John Duns Scotus, John Wyclif, Peter Auriol, Nicholas Bonet, Francisco Suárez, Francesco Patrizi, Giordano Bruno, Libert Froidmont, Marin Mersenne, Pierre Gassendi, Gottfried Wilhelm Leibniz and Samuel Clarke. We see how reflections on space, imagination and the cosmos were the product of a plurality of philosophical traditions that found themselves confronted with, and enriched by, various scientific and theological challenges which induced multiple conceptual adaptations and innovations. This volume is a useful resource for historians of philosophy, those with an interest in the history of science, and particularly those seeking to understand the historical background of the philosophy of space.